The association between experiencing violence and hypertension in urban South African adolescents - Chivafa, Adatia (My University, 2020)
Introduction: Experiencing violence in childhood has been shown in adult studies to be linked with the development of hypertension and other cardiovascular disease (CVD). Understanding this relationship in earlier years and especially in a country burdened by violence like South Africa (SA) could improve hypertension screening and support in adolescents who experience violence. This study, therefore, aims to determine the pathways through which experiences of violence affects blood pressure (BP) in 18-year-old adolescents in the Soweto-Johannesburg Metropolis. Materials and Methods: This study utilised data collected at a follow-up visit (at age 18) from an on-going longitudinal study on child and adolescent health and development, the Birth-to-Twenty plus cohort (BT20+). This study included all non-pregnant 18-year-olds with BP assessments at the 18th year follow-up visit. BP and anthropometric measures were collected by experienced assistants using standardised tools and other data collected through interviewer-administered face-to-face and self-administered questionnaires. Continuous variables were described using the mean and standard deviation (SD) or the median and interquartile range (IQR). Categorical variables were described using frequencies and percentages and they were all categorised by hypertension status. Structural equation modelling (SEM) and generalised structural equation modelling (GSEM) were used to determine the pathways through which violence affects BP. All estimates were evaluated at 5% level of significance.Results: After exclusions 1630 participants remained, 44% were female, 87% were black, and 22% percent used alcohol. Fifteen percent of the participants were hypertensive, 54% male and 46% female. Body mass index (BMI), waist-to-hip ratio (WHR), and parity were significantly higher (p<0.001, p<0.001, and p=0.006 respectively) among hypertensives. Income, however, was R2400 lower (p=0.044) among hypertensives when compared to normotensives. From the GSEM we found that experiences of violence had no statistically significant association with hypertension though the odds indicated an upward trend [OR: 1.01; CI: 0.97-1.06]. A unit increase in BMI was associated with an increase in odds [OR: 1.04; CI: 1.01-1.09] of hypertension. Sex mediated the association between experiences of violence and hypertension [OR: 0.61; CI: 0.53-0.69] also BMI and hypertension [OR: 15.09; CI: 8.99-25.31]. Alcohol use, in turn, mediated the association between experiences of violence and hypertension [OR: 0.87; CI: 0.78-.97].The SEM models also did not show any statistically significant associations between experiences of violence and SBP [β=-0.22; CI: -1.57-1.12] or DBP [β=0.66; CI: -0.509-1.828]. An increase in BMI was associated with an increase in SBP [β=0.729; CI: 0.55-0.90] and DBP [β=0.32; CI: 0.17-0.47], females had significantly lower SBP [β=-7.24; CI: -8.86 to -5.62] than males. Sex mediated the association between violence with SBP [β=-0.51; CI: -0.64 to -0.37] and DBP and the association between BMI with SBP [β=2.69; CI: 2.15-3.23] and DBP inversely. Adolescents born to mothers with more children also had an increased likelihood of having high SBP [β=0.86; CI: 0.09-1.64], while those born to single [β=-1.94; CI:-3.39 to -0.49], older [β=-0.16; CI: -0.17 to -0.02], and mothers with higher education [β=-3.02; CI: -5.77 to -0.27] had a reduced likelihood of having high DBP. Conclusions:Though there were no significant direct effects between experiencing violence and SBP, DBP, and hypertension among 18-year-old urban adolescents, study findings were indicative of an associated increase in hypertension and DBP with increasing experiences of violence. The mediation of sex between experiences of violence, BMI and the BP variables suggests two risk factors requiring intervention during adolescence. Interventions among males towards positive coping strategies and females towards weight control and body positivity early in life could see a significant decrease in the risk of developing hypertension.
This research report is submitted in part fulfilment of the requirements for the degree of Master of Science in Epidemiology in the field of Biostatistics to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2020